Analisis Komunikasi Kelompok Pada Komunitas Vespa Bengkulu Bersatu Dalam Membentuk Identitas Sosial - Trio Ardito; Sapta Sari; Dilmai Putra (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study analyzes how group communication within the Vespa Bengkulu Bersatu community contributes to shaping the members’ social identity. This research is grounded in Henri Tajfel’s Social Identity Theory, which consists of three main dimensions: social categorization, social identification, and social comparison. Using a qualitative approach, the study collected data through in-depth interviews, participatory observation, and documentation. The findings reveal that group communication strengthens solidarity, forms a collective image, and differentiates the group from others. Symbols, touring activities, shared values, jargon, and both offline and digital interactions play significant roles in shaping strong social identity and fostering a sense of belonging within the community.